SURGICAL APPROACH IN THE TREATMENT OF DEEP ENDOMETRIOSIS: CHALLENGES AND ADVANCES - Pedro do Valle Varela, João; Clara Berzoini Albuquerque, Ana; Sandoval Pickert, Fabio; Rezende, Danielle; Bandeira Lima, Julia; Oliveira Gil de Almeida, Yasmin; Lucindo Lakatos, Luiza; Carrara Folly Valente, Jaqueline; Augusto Rocha Pompermayer, Vinicius; Pereira Ramos Júnior, Sidney; Guimarães Cunha, Débora; Wagmacker Barbosa, Bárbara; et al. (Health and Society, 2025)
Deep endometriosis is a gynaecological condition characterized by the presence of endometrial tissue outside the uterus, involving organs such as the ovaries, intestines and bladder. The disease can cause chronic pain, infertility and additional complications, significantly affecting patients’ quality of life. Although clinical treatment, such as the use of hormones, is common, the surgical approach has become essential for cases of deep endometriosis, when symptoms are not effectively controlled. The aim of this study is to analyze the challenges and advances in surgical approaches to the treatment of deep endometriosis, focusing on innovative techniques, long-term efficacy and the multidisciplinary approach to managing the condition. This is a literature review with a qualitative approach, which will use the PubMed, Scopus and Web of Science databases to gather relevant articles on the surgical and psychological management of endometriosis. The search will be refined using health descriptors such as “Endometriosis Surgery,” “Deep Infiltrating Endometriosis,” “Psychological Impact,” among others, with a time frame between 2014 and 2021. The review aims to consolidate best practices and advances in the treatment of endometriosis, both in terms of surgical interventions and psychological approaches. Laparoscopic surgery has proven to be one of the main therapeutic options in the treatment of deep endometriosis, allowing precise removal of lesions with lower complication rates and faster recovery. Recent advances in robotic surgery have also contributed to greater precision and less tissue trauma. However, complete removal of lesions is not always possible, which can lead to recurrences. Treatment also requires a multidisciplinary approach, involving gynaecologists, urologists, proctologists and fertility specialists, for proper management and minimization of complications. The surgical approach to treating deep endometriosis continues to evolve, with technological innovations offering better results and recovery for patients. However, the complexity of the condition requires ongoing specialist follow-up and the combination of clinical and surgical treatments to ensure long-term efficacy and symptom reduction. Personalizing the treatment for each patient is fundamental to the successful management of the disease.